Market competition and financial stability: the case for Takaful (Islamic Insurance) market - Cheong, Sue Sim; Sheikh Hassan, Ahmad Fahmi (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2019)
The Takaful market has been growing substantially since its initiation and has begun gaining traction across the globe. Nevertheless, recent pressures for consolidation may bring about significant implications upon market competition, as well as economic and financial performances. As such, this study highlights the recent financial market failures and discusses the ambiguous link between competition and stability. Additionally, this study emphasizes the significance of competition in affecting the stability of Takaful operators to reinforce the comprehension of Takaful market behavior. This study provides important policy implications for regulators, investors, and other market participants to promote the progress of the Takaful sector.